Pergeseran Perilaku Konsumen Pada Masa Pandemi Covid-19 Ditinjau Berdasarkan Efek Bandwagon, Snob dan Veblen - Astri Srigustini; Iis Aisyah (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
The aim of this study was to determine the differences in the effect of Bandwagon, Snob, and Veblen by consumers on cycling and plant collecting based on gender, area of residence, income level and type of job during the Covid-19 pandemic. The method used in this study is survey with purposive sampling technique. Analysis of the data used in this study is the analysis of different tests (Chi Square). The study found out that consumer behavior during the Covid-19 pandemic, especially in cycling and plant collecting, was influenced by the Bandwagon, Snob and Veblen effect. Furthermore, the results of different tests based on area of residence, type of job, and income level show that there are differences in behavior of cycling and plant collecting. However, it is found that there is no difference on gender of respondents for the Bandwagon effect in plant collecting. It indicates that both males and females perform the activity for the Bandwagon effect. It shows that consumers make decisions on irrational thinking. Therefore, consumers must think rationally so that they will not be trapped in cognitive bias.